Impact Tip Speed Ratio in Performance Analysis for Horizontal Axis Wind Turbine (HAWT) with Optimal Twist and Tapered (OPT) Blade Shape - Mat Zin, Muhammad Al,Ain; Ishak, Izuan Amin; Mohammad Arafat, Mohammad Arafat; Samiran, Nor Afzanizam; Sahari, Norain (semarak ilmu, 2024)
Performance for Horizontal Axial Wind Turbine (HAWT) is influenced by the difference in tip speed ratio (TSR) and mesh distribution. The objective of this article is to study the optimal performance of wind turbines when subjected to different mesh resolution, TSR and wind speed velocity.Therefore, it is important to study the effects of different mesh resolutions in terms of wind turbine performance. To achieve that, a 0.65m optimal twist and tapered (OPT) blade is used with various inlet velocities and TSR. This study uses the k-ꞷ shear-stress transport (SST) based Reynold-Average Navier Stokes (RANS) approach in commercial ANSYS Fluent CFD software. This simulation was performed using the Moving Ratio Frame (MRF) method. To find the optimum grid resolution, a Grid Independence Test (GIT) was conducted comparing the coefficient of power (Cp). From the RESULT, TSR 6 shows the best HAWT performance when Cp for inlet velocity 8 m/s is 0.2608.